2020
DOI: 10.1097/sap.0000000000002592
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Wound Complications After Soft Tissue Sarcoma Resection

Abstract: Soft tissue sarcomas are a heterogenous group of malignant tumors that represent approximately 1% of adult malignancies. Although these tumors occur throughout the body, the majority involved the lower extremity. Management may involve amputation but more commonly often includes wide local resection by an oncologic surgeon and involvement of a plastic surgeon for reconstruction of larger and more complex defects. Postoperative wound complications are challenging for the surgeon and patient but also impact mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…The incidence of haematoma was very low in both the CB and CBD groups. This matches a previous study which reported four haematomas in 118 STT patients [ 6 ]. Therefore, another study with greater numbers of postoperative haematomas may be needed to accurately evaluate the effect of surgical drains.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The incidence of haematoma was very low in both the CB and CBD groups. This matches a previous study which reported four haematomas in 118 STT patients [ 6 ]. Therefore, another study with greater numbers of postoperative haematomas may be needed to accurately evaluate the effect of surgical drains.…”
Section: Discussionsupporting
confidence: 93%
“…Such complications include SSI, seroma, haematoma, and wound dehiscence, all of which can directly and indirectly adversely affect morbidity and mortality. Various risk factors affecting wound complication incidence have been documented, including tumour location, neoadjuvant chemotherapy, and radiotherapy [ 6 ]. When poorly managed, these complications may necessitate limb amputation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one series, wound complications were recorded in 43.3%. It was more common in cases of vascular reconstruction (34.5% vs 15.3%; p = 0.05) 10 .…”
Section: Survival and Effect Of Different Prognostic Factorsmentioning
confidence: 94%
“…39,46 The use of keystone flaps, propeller flaps, or local pedicle perforator flaps in the torso and extremity has been well-described and can be used just as reliably for sarcoma reconstruction. 46,47 However, in the setting when the resection is more extensive (>100 cm 2 in the upper extremity), especially to obtain clear margins, a free tissue transfer is often necessary, with numerous studies confirming high success rates despite prior radiation therapy. 34,[48][49][50][51] 1091e…”
Section: Reconstructive Algorithmmentioning
confidence: 99%